2009
DOI: 10.3346/jkms.2009.24.s1.s135
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Monitoring Circulating CD4+CD25+Regulatory T Cells in Kidney Transplantation during the Early Posttransplant Period

Abstract: The CD4+CD25+ T regulatory cells (Tregs) play an important role in immune tolerance in experimental transplantation but the clinical significance of circulating Tregs in the peripheral blood is undetermined. In 50 kidney transplant (KT) recipients, 29 healthy controls and 32 liver transplant (LT) recipients, the frequency of Tregs was measured with flow cytometry before and after transplantation. In the KT recipients, IL-10 secretion was measured with an enzyme-linked immunospot (ELISPOT) assay. The median fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 28 publications
1
21
1
Order By: Relevance
“…24 In addition, a significant difference was found between healthy control and chronic graft rejection patients in the current study, which agrees with findings of Karczewski and coworkers. 13 However, there was no significant Abbreviations: CSA, cyclosporine; Prog, prograf (tacrolimus); RAPA, rapamycin; stab, stable 6 but not with findings of other studies that found an increase in patients with graft acceptance 13,25 or a significant decrease of Tregs in transplant patients compared with healthy controls. 23 The variation between the different studies could be explained by the heavy immunosuppressive regimen posttransplant that may differ from 1 center to another and that affects Tregs.…”
Section: Discussionmentioning
confidence: 43%
See 4 more Smart Citations
“…24 In addition, a significant difference was found between healthy control and chronic graft rejection patients in the current study, which agrees with findings of Karczewski and coworkers. 13 However, there was no significant Abbreviations: CSA, cyclosporine; Prog, prograf (tacrolimus); RAPA, rapamycin; stab, stable 6 but not with findings of other studies that found an increase in patients with graft acceptance 13,25 or a significant decrease of Tregs in transplant patients compared with healthy controls. 23 The variation between the different studies could be explained by the heavy immunosuppressive regimen posttransplant that may differ from 1 center to another and that affects Tregs.…”
Section: Discussionmentioning
confidence: 43%
“…The results of our study revealed that neither the type of donor nor the presence of infection had an effect on circulating Tregs; this also was reported in other studies. 6,13,23 Regarding the effect of sex, we found no significant difference in Treg percentage between male and female patients. To study the effect of duration posttransplant on Tregs, we divided the patients according to the period posttransplant into 3 subgroups: < 5 years; 5 to 10 years; and > 10 years.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations